Pengaruh Penggunaan Beberapa Varietas dan Aplikasi Pseudomonas fluorescens untuk Mengendalikan Penyakit Bulai (Peronosclerospora maydis) pada Tanaman Jagung (Zea mays L.) - Muhamad Aditia Ulhaq; Rachmi Masnilah (Jurnal Pengendalian Hayati, 2019)
Corn is one of the commodities that have high economic value and important role in meeting food needs in Indonesia. Unfavorable conditions on the rate of the higher demand for corn. Pests to be one limiting factor that causes a decrease in the production of corn. Peronosclerospora maydis is a pathogen that causes downy mildew on corn. P. maydis infects corn plants at the age of 2-3 weeks, with the level of damage reaches 80-100%. Control efforts against this disease one of them using antagonistic microbes such as bacteria Pseudomonas fluorescens. P. fluorescens has the potential to control downy mildew because it produces compounds that are antibiosis as chitinase enzymes that can hydrolyze the cell walls of fungi. The purpose of this study to determine the effect of the interaction of P. fluorescens isolates applications and the use of some varieties to suppress downy mildew attack P. maydis on corn. The method used is to use a random test design of a factorial group with 2 factors. The first factor is the type of varieties with three levels namely V1: Pioneer 27, V2: Pioneer 21 and V3: Bonanza. The second factor is a type of isolates P. fluorescens with three levels namely P1: without the application of P. fluorescens, P2: Isolates P. fluorescens (A) and P3: Isolate of P. fluorescens (B). The result is the application of P. fluorescens and use of some varieties can suppress downy mildew P. maydis.